2019
DOI: 10.1097/jhq.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Use of Prehospital Telemedicine to Decrease Door to Computed Tomography Results in Acute Strokes

Abstract: Introduction: Timely emergency department (ED) recognition of acute strokes reduces morbidity and mortality and improves outcomes. Prehospital telehealth evaluation rapidly assesses patients with stroke symptoms and mobilizes resources before ED arrival, decreasing ED arrival to computed tomography (CT) result times. Expediting CT results reduces the decision time to determining thrombolytic therapy eligibility. Methods: Seventeen ambulances in our regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Telemedicine has been used to provide consultations, record and send vital signs and diagnostic tests, as well as interpret the results of CT scans, magnetic resonance imaging/MRI, and ECGs. 12,2227…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Telemedicine has been used to provide consultations, record and send vital signs and diagnostic tests, as well as interpret the results of CT scans, magnetic resonance imaging/MRI, and ECGs. 12,2227…”
Section: Discussionmentioning
confidence: 99%
“…Six studies were conducted in the United States 12,22,23,2527 and only one study was conducted in Germany. 24 Yang, et al’s study showed that the United States has the highest number of publications and citations in the field of digital health literacy and telemedicine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations